Politics and trade in Britain, 1776-1914.
1 online resource (xlviii, 296 pages)
Keywords: The period between 1880 and 1914, the subject of this volume, sees increasing questioning of free trade, especially in those sectors impacted adversely by foreign competition, and within political circles, where the notion of protecting native industries shifted from an agricultural to an industrial base. There was a greater willingness, especially in the Conservative party, to consider it as a viable policy. The ⁰́₈constituencies⁰́₉ or interest groups created by free trade however defended it fiercely among the Liberal party and in manufacturing industries, primarily those highly dependent on export markets. Debates on commercial policy in this period had another dimension which had been subsidiary in earlier periods⁰́₄the colonial empire and the economic, political, and cultural ties with it promoted. The period between 1880 and 1914 was one where the language of empire was at its height and the economic relationship between the Mother Country and the colonies entered political debate in a forceful way. The sources include several petitions from parliamentary papers attacking the system of commercial treaties pursued by the British government. Towards this end, extracts from the journal Fair Trade, and a body of newspaper material detailing extra-parliamentary movements against free trade, from the Leeds Mercury, Glasgow Herald, Pall Mall Gazette, and Daily Mail, are also included. Making the transition to the early twentieth century and the rise of the labour movement, printed sources such as Fabian tracts on tariff reform, as well as material from the International Free Trade Congress, are incorporated.